O Estudo da Entropia de Transferência em Sistemas Dinâmicos Discretos - Ferrari, Fabiano Alan Serafim (2012)
Chaotic systems are characterized by irregular behaviour, which some times are confused with random behaviour. The time evolution of these systems is described using an evolution rule. Even a chaotic system begins in two very close initial conditions, they will diverge exponentially to one another. Thus, this sensibility creates difficults to predict and get the chaotic orbit. Chaotic systems unpredictness make it more intersting studying its probability distribution than its time series directly. Through information theory is possible study dynamical systems by mean of its probability. Inside information theory an important quantity is the transfer entropy, that allows us to study statistic coherence in systemns which have their evolution through time. With this coherence it is possible transmit information using chaos in a safe way. Therefore, we present a model present in the literature and we suggest a new model of this safe transmission.